Decreased levels of NMDA but not AMPA receptors in the lipid-raft fraction of 3xTg-AD model of Alzheimer's disease: Relation to Arc/Arg3.1 protein expression. (November 2016) - Morin, Jean-Pascal; Díaz-Cintra, Sofía; Bermúdez-Rattoni, Federico; Delint-Ramírez, Ilse
Abstract: It was recently suggested that alteration in lipid raft composition in Alzheimer's disease may lead to perturbations in neurons signalosome, which may help explain the deficits observed in synaptic plasticity mechanisms and long-term memory impairments in AD models. As a first effort to address this issue, we evaluated lipid-raft contents of distinct NMDA and AMPA receptor subunits in the hippocampus of the 3xTg-AD model of Alzheimer's disease. Our results show that compared to controls, 10 months-old 3xTg-AD mice have diminished levels of NMDA receptors in rafts but not in post-synaptic density or total fractions. Additionally, the levels of GluR1 were unaltered in all the analyzed fractions. Finally, we went on to show that the diminished levels of NMDA receptors in rafts correlated with diminished global levels of Arc/Arg3.1, a synaptic protein with a central role in long-term memory formation. This study adds to our current understanding of the signaling pathways disruptions observed in current Alzheimer's disease models.